Quality changes of nugget prepared from fresh and smoked rainbow trout during chilled storage - Duman, Muhsine; Kuzgun, Nermin Karaton (Emerald Group Publishing Ltd, 2018)
Purpose The purpose of this paper is to produce fish nugget from fresh or smoked fish and to investigate the quality characteristics of fish nuggets during refrigerated storage. Design/methodology/approach The study was designed to evaluate the effect of fresh and smoked fish on the storage quality parameters of fish nuggets. The products were developed by incorporating optimum level of fresh and smoked separately and were vacuum packaged in low-density polyethylene pouches and assessed for various storage quality parameters under refrigerated (21 degrees C) conditions for 27 days of storage. The products were evaluated for various chemical, microbiological and sensory parameters at regular interval of three day. Findings Nuggets from smoked fish had lower (p<0.05) moisture, higher fat and crude protein compared to fresh fish nuggets. Total volatile basic nitrogen for fresh nugget samples exceeded the limit value of 30mgN/100g fish muscle on the 24 days of storage. At the end of storage period, TBA values were 2.8mg malonaldehyde/kg for fresh nugget samples and 2.1mg malonaldehyde/kg for smoked nugget samples. Microbial counts were found to be significantly (p<0.05) higher in fresh nugget than in smoked nugget samples. Sensory quality scores of smoked nuggets were significantly higher, than fresh nugget. The shelf life of fish nugget was found to be 24 days for fresh nuggets and 27 days for smoked nugget samples according to sensory assessment results. Originality/value The paper has demonstrated that the smoked fish meat prouduce nuggets of better quality, as indicated by lower microbial counts and higher sensory attributes compared to fresh fish meat.
Keywords: Quality control; Sensory evaluation